2012
DOI: 10.1136/bmjopen-2012-000958
|View full text |Cite
|
Sign up to set email alerts
|

The possible absence of a healthy-worker effect: a cross-sectional survey among educated Japanese women

Abstract: ObjectivesDespite being highly educated in comparison with women in other member countries of the Organisation for Economic Cooperation and Development, Japanese women are expected to assume traditional gender roles, and many dedicate themselves to full-time housewifery. Women working outside the home do so under poor conditions, and their health may not be better than that of housewives. This study compared the self-rated health status and health behaviours of housewives and working women in Japan.DesignCross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…The difference likely lies in caregiving and maternity leave, creating a far more complex scenario of potential confounding and selection bias in studying occupation and pregnancy outcomes. A recent study in Japan, for example, found little evidence of a healthy worker effect even among highly educated women, which the authors hypothesized might be due to strong social norms towards traditional caregiving/homemaking roles for women [Nishikitani et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference likely lies in caregiving and maternity leave, creating a far more complex scenario of potential confounding and selection bias in studying occupation and pregnancy outcomes. A recent study in Japan, for example, found little evidence of a healthy worker effect even among highly educated women, which the authors hypothesized might be due to strong social norms towards traditional caregiving/homemaking roles for women [Nishikitani et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies in which healthy worker biases cannot be well accounted for (e.g., some occupational cohorts), making valid comparisons of results between studies might be challenging, given the observations of this and other studies suggesting that the magnitude of bias might vary by population characteristics [6,7]. …”
Section: Discussionmentioning
confidence: 99%
“…However, in many populations, substantial proportions of healthy women opt out of the workforce for reasons unrelated to health, such as to provide childcare [5]. Investigators have also found evidence suggestive of weaker healthy worker biases caused by healthy women leaving the workforce after marriage among U.S. white women in the 1960s and in a contemporary population of college-educated Japanese women [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Owing to various work preferences, both regularly employed and non-regularly employed women had different factors that threatened their health. A previous nationally representative survey suggested that a shift toward diverse employment patterns might be a cause of deteriorating health among the entire working population, regardless of employment status14 ) .…”
Section: Findings From Previous Studies: Associations Between Non-regmentioning
confidence: 99%